How to succeed at medical school : an essential guide to learning - Evans, Dason. 4 0 16; 1957- Brown, Jo; 5 (Chichester, UK:;Hoboken, NJ : BMJ/Wiley-Blackwell, 2009)
Contains tips, exercises, and techniques to help students in medical school survive and excel.
What kind of learner are you? -- Learning knowledge -- Learning clinical skills -- Learning clinical communication skills -- Working in a group -- Developing your academic writing skills -- Portfolios and reflection -- Life-work balance -- Revision -- Exam technique : general rules -- Exam technique : specific examples -- Thinking ahead : student-selected components, careers and electives.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; methods.;Study and teaching. -- Medical education.;Medical students.;Medical colleges.;Learning.;Education, Medical;Learning.;Medicine;Medical students.;Medical colleges.;Learning and scholarship; 20; 2